Microbial carbon use efficiency in grassland soils subjected to nitrogen and phosphorus additions. (July 2020) - Widdig, Meike; Schleuss, Per-M.; Biederman, Lori A.; Borer, Elizabeth T.; Crawley, Michael J.; Kirkman, Kevin P.; Seabloom, Eric W.; Wragg, Peter D.; Spohn, Marie
Abstract: Soil microbial carbon use efficiency (CUE), defined as the ratio between carbon (C) allocated to growth and C taken up by microorganisms, is pivotal for the understanding of C cycling in terrestrial ecosystems. Soil microbial CUE is thought to increase under nitrogen (N) addition, thereby mediating the effects of atmospheric N deposition on C cycling in soils. We studied the effects of N, phosphorus (P), and combined N and P addition on soil microbial CUE from a total of six grassland soils from South Africa, USA, and UK. Microbial CUE varied between 25 and 57% with a mean value of 40% across all sites, depth increments, and treatments. Most of the site variability in microbial CUE was explained by sand content, mean annual precipitation and temperature, and the dissolved organic C:dissolved N ratio. Soil microbial CUE as well as microbial biomass turnover time were robust to changes in N, P, and NP supply. However, N addition significantly reduced microbial respiration and C uptake in the topsoil. Taken together, N, P, and NP addition did not influence microbial CUE and biomass turnover time in grassland soils on different continents, indicating that microbial CUE varies little despite large changes in element inputs. Consequently, increased N inputs to soil may have a smaller impact on microbial CUE and biomass turnover time, and therefore C cycling in grassland soils, than expected and models assuming increased CUE with increasing N inputs could overestimate future C storage. Graphical abstract: Image 1 Highlights: Soil microbial CUE was measured by incorporation of 18 O–H2 O into microbial DNA. Neither N nor P additions changed microbial CUE in grasslands on three continents. Microbial respiration and C uptake both decreased under N addition. Sand content, MAP, MAT, and DOC:DN ratio explained 70% of the variability in CUE. Microbial biomass turnover time was not affected by N and P addition.